2007
DOI: 10.1016/j.jacc.2007.03.063
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Mechanical Circulatory Support for Inotrope-Dependent Heart Failure Patients Who Are Not Transplant Candidates

Abstract: Inotrope-dependent heart failure patients who are ineligible for transplantation have a high short-term mortality rate and derive a significant survival advantage from "destination" mechanical circulatory support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
173
0
16

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 305 publications
(190 citation statements)
references
References 23 publications
1
173
0
16
Order By: Relevance
“…8 Initial clinical trials of older pulsatile flow LVADs used as destination therapy demonstrated 1-year survival of 52%, 9 and more recent studies of continuous flow pumps, used for the same indication, showed 1-year survival of 73%. 10 These studies also documented improvements in functionality and quality of life relative to that seen with medicallytreated HF.…”
mentioning
confidence: 99%
“…8 Initial clinical trials of older pulsatile flow LVADs used as destination therapy demonstrated 1-year survival of 52%, 9 and more recent studies of continuous flow pumps, used for the same indication, showed 1-year survival of 73%. 10 These studies also documented improvements in functionality and quality of life relative to that seen with medicallytreated HF.…”
mentioning
confidence: 99%
“…Specifically, the showed an 82% 1 year freedom from device malfunction [9]. A similar trial was undertaken with the Novacor™ system called INTrEPID (Investigation of Nontransplant-Eligible Patients Who Are Inotrope Dependent)-like REMATCH, LVAD survival was superior to optimal medical therapy at one year (27% vs 11%) [10] (Figure 1). …”
Section: The First Generation Implantable Lvadsmentioning
confidence: 98%
“…A total of 85% of the LVAD-treated patients had minimal or no heart-failure symptoms. Five Novacor ® patients and one OMT patient improved sufficiently while on therapy to qualify for cardiac transplantation [15]. The Randomized Evaluation of Mechanical Assistance for the Treatment of Congestive Heart Failure (REMATCH) trial have also demonstrated that implantation of the HeartMate XVE LVAD, as destination therapy, can provide survival superior to any known medical treatment in patients with end-stage heart failure who are ineligible for transplantation [16].…”
Section: Surgical Management Of Congestive Heart Failurementioning
confidence: 99%
“…Whereas the role for LVADs as a bridge-to-transplantation has been established, the data supporting their role as permanent therapy in nontransplant candidates is still limited. The Investigation of Nontransplant-Eligible Patients Who Are Inotrope Dependent (INTrEPID) trial was a prospective, nonrandomized clinical trial comparing LVAD with optimal medical therapy (OMT) [15]. A total of 55 patients with NYHA functional class IV symptoms who failed weaning from inotropic support were offered a Novacor LVAD.…”
mentioning
confidence: 99%